Metalinguistic function of language in the teaching and assessment of speaking skills in foreign languages - Gaínza Lastre , M. Sc. Luis Manuel; Montejo Lorenzo , Dr. C. Manuel Narciso (Transformación, 2024)
The paper presents a comparative study of different techniques of error correction in English lessons and a proposal of strategies for negotiation of meaning based on the metalinguistic function of language. A preexperiment was conducted in three consecutive academic years, in which the tendencies under analysis were implemented. A critical assessment and recommendations are made on the basis of the results obtained. .
Keywords: Evaluation; oral expression; functions of language; negotiation of meaning